Screening of biomarkers for early diagnosis of trauma-induced coagulopathy based on untargeted metabolomics - Xu, Xu; Ouyang, Qianhui; Shao, Min; Yi, Qi; Liu, Sixiang; Huang, Ying; Wang, Jia; Zhang, Xingwen; Tan, Chaochao (Frontiers in Endocrinology, 2025)
ObjectivesTrauma-induced coagulopathy (TIC) is an acute coagulation disorder characterized by massive bleeding following trauma and is a leading cause of mortality. However, current clinical methods are inadequate for predicting TIC onset, and reliable biomarkers for early diagnosis are lacking. This study aimed to identify potential biomarkers with high sensitivity and specificity for TIC using an untargeted metabolomics approach.MethodsWe analyzed serum samples from 54 trauma patients (27 with TIC and 27 without TIC) and 27 healthy controls. All samples were collected within 24 hours post-trauma. Metabolomic profiling was conducted using liquid chromatography-tandem mass spectrometry (LC-MS).ResultsMetabolite profiles differed significantly between the TIC and non-TIC groups. Two metabolites, LysoPE(20:4(8Z,11Z,14Z,17Z)/0:0) (AUC = 0.933, 95% CI: 0.849–0.995) and LysoPE(0:0/18:2(9Z,12Z)) (AUC = 0.916, 95% CI: 0.818–0.914), were identified as potential biomarkers for distinguishing TIC. The diagnostic performance of these metabolites surpassed that of both conventional coagulation tests and admission assessment scores.ConclusionTwo LysoPE metabolites were identified as promising biomarkers for the early detection of TIC.